OCCURRENCE OF EPILITHIC DIATOMS IN A STREAM WITH CLEAN WATER CONDITIONS: HARINGET STREAM, TURKEY - Sonmez, Feray (Parlar Scientific Publications (P S P), 2017)
In the study, species composition of diatoms and their seasonal variations in epilithic associations occurring in a clean water stream (Haringet) were determined between January and December 2014. Sampling was performed monthly at three stations chosen in upper, middle and lower parts of the stream. Water temperature, pH, electrical conductivity, total dissolved solid matter, dissolved oxygen, flow rate, total hardness, total alkalinity, organic matter, salinity, nitrate, ortho-phosphate, sulfate and silica values in water were measured and analysed monthly. A total of 48 diatom taxa all belonging to pennales were identified throughout the study. Members of the genera Cymbella, Diatoma, Epithemia, Gomphonema, Navicula, Nitzschia and Surirella were common epilithic diatoms in the Stream. Nitzschia was the richest in species composition. Cocconeis pediculus, Cymbella affinis, C. helvetica, Diatoma elongata, Fragilaria acus, Gomphonema intricatum, G. olivaceum, Navicula radiosa, Nitzschia sigmoidea and Ulnaria ulna were noticable diatoms with respect to frequency of occurence and individual numbers in epilithon at all stations. Variations in occurrence of diatom species and their abundance were compared at stations and discussed in relation to physical and chemical properties of stream water. The physicochemical values yielded that Haringet Stream has Class I Water Quality according to the Inland Water Quality Criteria. This finding is somehow supported by the occurrence of certain clean water diatom species.
Keywords: Epilithon; Diatom; seasonal succession; Haringet Stream; Turkey